The Influence Of Online Learning Interaction On Learning Outcomes And Learning Continuation Intention Of Chinese Higher Institutions Students - Junjie, Pan (2024)
Online learning is a hot topic in the education circle, and higher institutions students, as the largest user group of online learning, have also received continuous attention from the education circle on their use of online learning platforms. Now, due to many problems exposed in the online learning environment, more and more higher institutions students' learning outcomes and learning continuation intention have significantly decreased. Although previous studies have established the link between online learning interaction, learning outcomes and learning continuation intention, little is known about the research on how online learning interaction affects higher institutions students' learning outcomes and learning continuation intention through perceived usefulness and perceived ease of use. To fill this gap, this study explores the relationships among online learning interaction, perceived usefulness, perceived ease of use, learning outcomes, and learning continuation intention. This research adopts the technology acceptance model (tam) and moore’s model of interaction to construct the theoretical model. This study aims to analyze characteristics of perceived usefulness and perceived ease of use as a mediator of the relationship between higher education students' learning outcomes and learning continuation intention